Ethical Considerations in Digital Marketing: Challenges and Best Practices - Preeti vats, Monika Sharma, Mansi Batra Kawatra; Manoj Sathe, Suchita Arora, Ashok Kumar Sahoo (Journal of Informatics Education and Research, 2024)
The use of technological devices and platforms for user participation, transfer of knowledge, and data exchange is referred to as online ethics. Social media platforms may be digital marketing instruments to identify trends, client interactions, and market demands. Cyberbullying is a serious topic, however, the majority of studies have concentrated on worries related to consumer privacy. It is crucial to use ethical decision-making methods before participating in any type of web-based activity because of how simple and quick these activities are. This essay seeks to examine the expenses associated with social media websites that rely on internet-based technology, as well as any possible drawbacks and moral dilemmas. The research looks at ethical issues including laws, rules, and privacy-regulating insurance plans. Consumer worries regarding the moral implications of internet purchases have increased along with e-commerce. The article uses a comprehensive examination of the literature on digital advertising, social networking sites, and ethics.